EFEKTIVITAS MODEL ASSURE TERHADAP KEMAMPUAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK PADA PEMBELAJARAN PAI - Ulya Fajriah; Listiyani Siti Romlah; Zulhannan Zulhannan; Didik Wahyudi (Jurnal Bilqolam Pendidikan Islam, 2026)
This research is motivated by the low interpersonal communication skills of students, characterized by passive attitudes, minimal participation, and lack of confidence in expressing opinions. This is due to the use of conventional teaching methods that are still dominated by the lecture method. This study aims to determine the effectiveness of the ASSURE model on students' interpersonal communication skills in PAI learning at SMAN 1 Pardasuka. This study uses a quantitative approach with a quasi-experimental method and a Posttest Only Control Group Design. The research sample consists of 60 eleventh-grade students selected thru cluster random sampling, with class XI-2 as the experimental class (ASSURE model) and class XI-3 as the control class (conventional learning). The instrument in the form of an interpersonal communication questionnaire with 22 valid items based on DeVito's theory, namely openness, empathy, supportive attitude, positive attitude, and equality, with a Cronbach’s Alpha reliability of 0.797. The results of the Independent Samples T-Test show a Sig. (2-tailed) value of 0.005 < 0.05, thus H0 is rejected and Ha is accepted, which proves that the ASSURE learning model is effective in improving students' interpersonal communication skills in PAI learning.